2008
DOI: 10.1007/s00432-008-0446-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between the expression of IL-10 and T cell activation proteins loss in early breast cancer patients

Abstract: Breast cancer patients may express abnormal cellular immune responses affecting their immunological competence. The analysis of immunological parameters may be useful as indicators of T cell function. To determine the expression of lymphocyte activation proteins and cytokines in tumor and non-metastatic axillary lymph nodes, 30 breast cancer patients were monitored. CD3 polypeptides, PTKs (protein tyrosine kinases) and phosphorylated tyrosines were studied by Western Blot and cytokines mRNA expression was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Residual cancer cells can be eliminated by effector cells after recognition by the host immune system in breast cancer as well as in other cancers . The underlying mechanism mediated by the suppression of the anti‐tumor immune system has been elucidated, and suppression of the host immune system is known to induce tumor relapse postoperatively . The postoperative relapse involving an immunological mechanism is difficult to eliminate because of the stimulation of residual cancer cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Residual cancer cells can be eliminated by effector cells after recognition by the host immune system in breast cancer as well as in other cancers . The underlying mechanism mediated by the suppression of the anti‐tumor immune system has been elucidated, and suppression of the host immune system is known to induce tumor relapse postoperatively . The postoperative relapse involving an immunological mechanism is difficult to eliminate because of the stimulation of residual cancer cells.…”
mentioning
confidence: 99%
“…5,6 The underlying mechanism mediated by the suppression of the anti-tumor immune system has been elucidated, and suppression of the host immune system is known to induce tumor relapse postoperatively. [7][8][9][10] The postoperative relapse involving an immunological mechanism is difficult to eliminate because of the stimulation of residual cancer cells. Among the mechanisms by which tumors evade the anticancer host immune system, ectopic expression of non-classical human leukocyte antigen (HLA) class Ib proteins (HLA-E, HLA-F and HLA-G) on cancer cells has been studied extensively.…”
mentioning
confidence: 99%
“…For example, in breast cancer, the expression of IL-10 was proven to be elevated through immunohistochemistry [43]. In addition, it was shown that patients with leukemias including acute myeloid leukemia (AML) and adult T-cell leukemia/lymphoma (ATLL) exhibited high levels of IL-10 in their serum [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer pathogenesis involves multiple factors including genetic, environmental, dietetic and immunologic (Hill et al, 2004;Grant et al, 2007;Llanes-Fernandez et al, 2009). Deficient DNA repair contributes to accumulation of DNA damage resulting in breast carcinogenesis and LOH (loss of heterozygosity), combined with allele silencing of tumour suppressor genes, may play a role in the progression of breast cancer (Driouch et al, 1997;Ahomadegbe et al, 2000).…”
Section: Introductionmentioning
confidence: 99%